TRANSFORMASI PELAYANAN PUBLIK: MENINGKATKAN KUALITAS LAYANAN PERCEPATAN PASPOR MELALUI OPTIMALISASI KOMUNIKASI DI ULP MAL PLAZA SEMANGGI - Mastur, Anida Sri Rahayu; Reynara, Regan Hagai (Polteknik Imigrasi, 2024)
Abstract. Public service is essential in fostering effective interaction between the government and society, particularly in maintaining service quality. Law Number 25 of 2009 emphasizes the importance of public trust in service providers. This study focuses on implementing expedited passport services to enhance service quality at the Passport Service Unit (ULP) in Plaza Semanggi Mall, under the Central Jakarta Class I Non-TPI Immigration Office. Using Edward III’s communication theory and service quality evaluation, this research identifies key challenges faced by applicants, notably in payment processes and infrastructure limitations. Through a descriptive qualitative approach, the study reveals the role of communication and efforts made to improve service quality. Recommendations include providing clearer payment instructions and increasing print media to support applicant guidance.